Description of a fossil camelid from the Pleistocene of Argentina, and a cladistic analysis of the Camelinae - Sinéad Lynch; Marcelo R. Sánchez-Villagra; Ana Balcarcel (Swiss Journal of Palaeontology, 2020)
Abstract We describe a well-preserved South American Lamini partial skeleton (PIMUZ A/V 4165) from the Ensenadan (~ 1.95–1.77 to 0.4 Mya) of Argentina. The specimen is comprised of a nearly complete skull and mandible with full tooth rows, multiple elements of anterior and posterior limbs, and a scapula. We tested this specimen’s phylogenetic position and hypothesized it to be more closely related to Lama guanicoe and Vicugna vicugna than to Hemiauchenia paradoxa. We formulate a hypothesis for the placement of PIMUZ A/V 4165 within Camelinae in a cladistic analysis based on craniomandibular and dental characters and propose that future systematic studies consider this specimen as representing a new species. For the first time in a morphological phylogeny, we code terminal taxa at the species level for the following genera: Camelops, Aepycamelus, Pleiolama, Procamelus, and Alforjas. Our results indicate a divergence between Lamini and Camelini predating the Barstovian (16 Mya). Camelops appears as monophyletic within the Camelini. Alforjas taylori falls out as a basal member of Camelinae—neither as a Lamini nor Camelini. Pleiolama is polyphyletic, with Pleiolama vera as a basal Lamini and Pleiolama mckennai in a more nested position within the Lamini. Aepycamelus and Procamelus are respectively polyphyletic and paraphyletic. Together, they are part of a group of North American Lamini from the Miocene epoch.